Cluster Headache in Kuwait: A Hospital-Based Study - Al-Hashel, Jasem; Ibrahim, Ismail; Youssry, Doaa; Ahmed, Samar Farouk; Goadsby, Peter (Frontiers in Neurology, 2019)
Background: Cluster headache (CH) is a relatively uncommon primary headache disorder. Few studies in our region described CH. We aimed to study demographics, clinical characteristics and treatment modalities of CH patients referred to Headache Clinic in Kuwait. Materials and Methods: This cross-sectional study included all CH patients who are referred to headache clinic. The diagnosis of CH based on the CH diagnostic criteria of the Headache Classification Committee of the IHS, 3rd edition (beta version) (ICHD-3-beta). The demographics, clinical characteristics and treatment modalities of CH patients were recorded. Results: Forty six patients were diagnosed with CH which constituted 1.7% of all headache patients and 0.1% of all visits to Neurology clinic. Male:Female ratio was 15.3:1. Mean age was 40.1 ± 10.7 years and mean age at onset was 29 years (20–49). Family history was positive in 6.5%. Smoking was seen in 63.0% of patients while 6.5 % reported alcohol intake. CH was episodic in 84.4% and chronic in 15.2%. Seasonal predilection was seen in all patients; the most frequent season was Autumn 47.8%. The mean duration of the cluster bouts was 6 weeks (2–12 weeks). The mean duration of the attack was 60 min (15–180 min). Number of attacks per day ranged from 2 to 10 attacks with a mean of 5 attacks/day. The median of attack severity by Visual Analog Scale (VAS) was 8.5 (7–10). The time taken to diagnose the patients ranged from <1 year to 12 years with a mean of 4 years. Chronic CH have a statically significant relation with smoking (P = 0.036), older age (P = 0.027), and longer time taken to diagnosis (P = 0.026) compared to episodic CH. Conclusion: Our results reported that there is higher proportion of males compared to females and less positive family history. Smoking was a significant risk factor for chronicity in addition to advanced age, higher age at disease onset and a longer time taken till diagnosis.